A LOUCURA COMO FORMA-DE-VIDA: RESSONÂNCIAS PROFANAS EM GIORGIO AGAMBEN E GILLES DELEUZE - CATENACI, Giovanni Felipe (2020)
This text aims to present the plausibility of the following thesis: It is possible to conceive schizophrenia, as defined by Gilles Deleuze, in resonance with the idea of life form postulated by Giorgio Agamben. Conceptually, such statements go back to the fact of secularization, inserting into the world unsuspected airs of sacredness and violence, which in our view makes pertinent the approximate effort of the theses of these two authors; that despite their theoretical divergences, seem to dialogue as we will see, in relation to the diagnoses and exits to the problems of the contemporary. From the text Absolute Immanence, in which Agamben makes a comment to Immanence: a life... which, by the way, is the last text written by Deleuze, we will seek to draw a neighborhood zone between them, through which we will continue our analysis. Finally, we aim to demonstrate that the madness in Deleuze can be read from Agamben's perspective as a life-form, that is, as a life which, as it is lived in the immanence of its form, is capable of profaning, that is, render the religious devices of the control society inoperable, thereby liberating the vital power that is biopolitically imprisoned by the permanent State of Exception in which we live.